TUGAS DAN FUNGSI KEUCHIK, TUHA PEUET DALAM PENYELENGGARAAN PEMERINTAHAN GAMPONG LAMPISANG KECAMATAN PEUKAN BADA KABUPATEN ACEH BESAR BERDASARKAN QANUN NOMOR 8 TAHUN 2004 TENTANG PEMERINTAHAN GAMPONG - Andri Kurniawan (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Aceh is a province which is the unity of the legal community who are privileged and given special authority to organize and manage their own affairs and interests of its people in accordance with laws and regulations in the system and the principle of the Unitary Republic of Indonesia based on the 1945. Aceh Besar district government has issued Qanun Aceh Besar District No. 8 of 2004 on Village Governance, which is the translation of NAD Province Qanun No. 5 Year 2003. Qanun District No. 8 of 2004 on Village Governance is still valid until now. This is because the district has not revised the Qanun Aceh Besar district as mandated by Law Number 11 Year 2006 about the existing Governing Aceh.Keywords: Roles and Functions, Keuchik, Tuha Peuet, Village Governance.